1996
DOI: 10.1016/s0741-5214(96)80048-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carotid artery geometry on the magnitude and distribution of wall shear stress gradients

Abstract: These results indicate that flow disturbances in general and wall shear stress gradients in particular are markedly reduced in carotid artery bifurcations that are smooth and gradually tapered and do not have a bulb. Abrupt geometric wall changes such as those occurring in the normal carotid bulb and at the distal end of a patch-reconstruction after carotid endarterectomy are harbingers of disturbed flow and high wall shear stress gradients. These results suggest that carotid endarterectomy reconstruction geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
44
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 26 publications
3
44
0
2
Order By: Relevance
“…The potential roles of high-versus low-shear stress gradients in vascular biology are flow patterns in the lesion-prone areas that are disturbed by high spatial and temporal shear stress gradients and flow patterns in lesionresistant areas being steady laminar flows with low-shear stress gradients. 30,31 Thus, our study supports the hypothesis that the focal distribution of lipids in the arterial tree is due in part to local flow patterns.…”
Section: Discussionsupporting
confidence: 84%
“…The potential roles of high-versus low-shear stress gradients in vascular biology are flow patterns in the lesion-prone areas that are disturbed by high spatial and temporal shear stress gradients and flow patterns in lesionresistant areas being steady laminar flows with low-shear stress gradients. 30,31 Thus, our study supports the hypothesis that the focal distribution of lipids in the arterial tree is due in part to local flow patterns.…”
Section: Discussionsupporting
confidence: 84%
“…To simplify our model, rigid walls and Newtonian blood rheology were assumed, and these are generally considered reasonable approximations for the purposes of predicting WSS patterns to within 15% accuracy (33)(34)(35)(36)(37)(38)(39). However, it has been recently demonstrated that pulse propagation effects induced by vessel distensibility can lead to phase shifts between the proximal CCA and ICA/ECA flow waveforms (40), which might account for our need to apply an ad hoc correction to the measured waveforms to ensure mass conservation at all times.…”
Section: Discussionmentioning
confidence: 99%
“…4 -7,37 Moreover, the disturbed flow patterns associated with shear stress gradients appear to contribute to the growth of the atherosclerotic plaque. 38 We designed our study with these issues in mind: comparable operative procedures in all arteries, stainless steel Goldblatt clamps to standardize and minimize any potential reaction to the collar material, and application of the equivalent amount of stenosis to produce a uniform alteration of shear stress in all arteries. It is clear from our studies that under these conditions, vWF is not essential for neointimal formation.…”
Section: Discussionmentioning
confidence: 99%